Assessment of food habits and intensity of physical activity among private school-going adolescents of Bhubaneswar city: A cross-sectional study - Spandan Mishra; Alpana Mishra; Basanta Kumar Behera (Indian Journal of Community and Family Medicine)
Background: A major global risk factor for mortality, inadequate physical activity is increasing in many low- and middle-income nations, including India. This is contributing to the burden of noncommunicable diseases and negatively impacting global health overall. The objectives of the study are to assess the food habits and intensity of physical activity among school-going adolescents aged 12–15 years in Bhubaneswar. Material and Methods: The cross-sectional study was done among school-going adolescents aged 12–15 years in the private schools of Bhubaneswar City, Odisha. Two hundred participants were selected from two schools from two different zones of Bhubaneswar. The selected participants were administered with a Madras Physical Activity Questionnaire along with nutrition-related questions from 2006 India and Central Board of Secondary Education Global School-based Student Health Survey Questionnaire. Results: Out of 200 participants, 119 were male (64%) and 81 were female (36%), with a mean age of 14.05 years participated in the study with a mean body mass index (BMI) of male and female participants was 23.00 kg/m2 and 21.85 kg/m2, respectively. Similarly, the mean BMI of early and late adolescent age groups was 21.77 kg/m2 and 22.71 kg/m2, respectively. Sixty-three (70.8%) participants of mid adolescents performed inadequate physical activities under the school curriculum in comparison to early adolescents with a P value statistically significant (0.001). Out of 200 participants, 117 (58.5%) had inappropriate dietary habits of eating vegetables and fruit on a daily basis. Ninety (45%) participants were consuming drinking carbonated soft drinks such as Pepsi, Coca Cola, Sprite, and Coke for more than twice a week. Sixty-six (33%) participants skipped their breakfast for more than twice a week. The present study involves school-going adolescents to assess their physical activity and the dietary patterns followed by them. The dietary pattern was also enquired through a validated questionnaire for the previous week, giving an overview of 7 days dietary cycle. Most of the students belong to higher socioeconomic strata and reading in private (self-funded) schools. Conclusion: The dietary behavior, specifically consumption of fruits and vegetables and fast foods, was significantly associated with mid-adolescence and male gender. Health education and creating opportunities for physical education among students will improve the physical activity pattern. Further qualitative study may be conducted to explore the barriers and factors for this physical activity and dietary pattern among school-going adolescents.